The Profitability Comparison Between Islamic banking bank and Convetional Bank in Indonesia from 2004 - 2014 - Sena, Muhamad Ridho Chandra; Fathurohman, Taufik (Journal of Business and Management, 2016)
Abstract. Islamic Bank has grown quickly in all over the world including Indonesia. Islamic Bank not only exists in countries where Muslims are the majority but also in countries where Muslims are minority such as the United Kingdom and Japan. Islamic Bank grows significantly with the pace of 10 to 15% every year from 1997 to 2007, and it hopes that it will remain consistent focused growth in the future. In 1991, the first Islamic Bank that established in Indonesia was Bank Muamalat Indonesia and that year was the introduction of dual banking system era in Indonesia. As Islamic Bank in Indonesia keeps growing, the profitability performance should also increase. Therefore, this research focuses on analyzing and compare profitability between Islamic Bank and Conventional Bank. This research includes the most recent data that cover financial report from 2004 to 2014 to observe the performance of Islamic Bank and Conventional Bank in Indonesia. The profitability ratios applied in this research are Return on Assets (ROA), Return on Equity (ROE), Profit Margin (PM), Return on Deposit (ROD), and Net Operating Margin (NOM). This research observed all banks in Indonesia with available data. This study covers 1523 banks that include 1228 Conventional Banks, 78 Islamic Banks, and 217 Islamic Business Unit (IBU). The finding of this research shows that there are differences between Islamic Bank and Conventional Bank in each ratio that variates through the year.Â Keywords: Islamic Bank, Profitability, Financial Ratios